Рід Rosa L. (Rosaceae) у флорі Тернопільського плато - Sobko, V.G.; Kluyenko, O.V.; Yavorivskiy, R.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
In the Ternopol' plateau flora were found 34 species of genus Rosa L. The analysis of species polymorphism, ecological adaptations and endemicity is shown genetic bounds of species of section Caninae Crep. with dogroses of broad-leaved woods in Western Europe and of species of section Gallicanae DC. with rocky dogroses in Eastern Mediterranean.